Forward Modelling on Gravity Anomalies Fault Model Using MATLAB Mathworks: Forward Modelling pada Anomali Gayaberat Model Fault Menggunakan Matlab Mathworks (JURNAL GEOCELEBES, 2022)
The gravity method is one of the geophysical methods utilized to determine the subsurface conditions of the earth according to differences in rock mass density below the surface. In the exploration of gravity requires an initial description as a reference for measurement. The synthetic modelling carried out this time is a forward modelling of fault anomalies carried out with the help of Grav2dc and Matlab Mathworks software. This study aims to compare the results of synthetic modelling using Grav2dc software and Matlab Mathworks as well as to test whether the program built can run well or not. The model parameters utilized are the density value of 1 kg/m3 with a deep plate depth of 50 m, a shallow plate depth of 150 m and the location of the fault at a depth of 150 m with a thickness of 40 m. The data processing in this study used two pieces of software, are Grav2dc and Matlab MathWorks to compare and test whether the processing results using Matlab MathWorks software were in accordance with the synthetic model processed using Grav2dc software. The results obtained from this study are the fault model obtained from processing using Matlab MathWorks and Grav2dc software with model parameters in the form of density and depth, where density and depth have a role in shaping the value of the change in gravity.